O processo de formação docente na visão dos acadêmicos do curso de Letras em uma universidade pública no Estado do Paraná - Engelmann, Priscila do Carmo Moreira (2012)
The objective of the present study was to analyze, from undergraduate students’ perspective, how the language course at a public university in the state of Paraná prepares future teachers for the educational context influenced by social changes characterized by the advance of science and technology. The importance of the study is justified by the need to verify how the undergraduate courses, mainly in the area of humanities, have dealt with the legal issues that drive the process of teacher training to develop competences for teaching practice taking into account that this practice is constantly influenced by the social changes related to advances in science and technology. The methodological approach was qualitative. The data was collected through semi-structured individual interviews. The participants of the study were students of the final year of the Language Course. The main findings showed that the participants have a critical perception regarding the competences required for the preparation of what they consider to be a good teacher, but feel insecure about their training for future teaching practice. Another issue highlighted by the interviewees was the lack of relationship between theory and practice, as well as the lack of interdisciplinary practice in the course. The concepts of science and technology are present in the Law of Guidelines and Bases of Education (Law 9.394/1996) and also in the National Curriculum Parameters (PCN). Nevertheless, the National Curriculum Guideline for teacher training does not address these concepts, leaving it to Institutions of Higher Education the decision to work for the dissemination of knowledge related to science and technology. There is a need to address teacher education to a more interdisciplinary and problem-solving orientation, seeking improvements in the training process for future teaching practice. The evidences also showed that there is a gap between the construction of content knowledge and pedagogical knowledge and that the democratization of the concepts of science and technology were not part of the process of teacher training in that course. All these evidences pointed to the need for deeper reflections on the process of teacher education in relation to training for practice, focused on the educational context influenced by changes in science and technology.